Immigration and the Distribution of Incomes - Francine D. Blau; Lawrence Kahn (Center for Economic Studies and ifo Institute (CESifo), 2013)
Immigration may impact income distribution both by affecting the skill composition of a country's residents, and, by changing relative factor supplies, its relative factor prices. We provide some background evidence on compositional factors but focus primarily on factor prices. We first consider the economic theory of the impact of immigration on factor prices and the research methodologies, including structural and natural experiment approaches, used to estimate the impact of immigration on the native income distribution. We then survey the evidence on this question for several countries, and conclude by examining the impact of emigration on income distribution in the source country.
Keywords: D33; J61; 330; international migration; factor income distribution